PEMBELAJARAN KONTEKSTUAL TIPE SURVEY, QUESTION, READ, RECITE, DAN REVIEW UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MEMBACA SISWA - Dina M Sitorus,; Achmad Yudhi,; Nursyam Anaguna, (JOEL: Journal of Educational and Language Research, 2023)
The low reading passion effects the reading comprehension skiil of students grade 5th SDN 174559 Sirait Uruk which is the priority problem of the researcher. To solve this problem, the research was done about application of contextual learning SQ3R type, to improve students’ reading comprehension skill, students’ motivation to learn especially reading, and teacher’s professional skill. The research method is classroom action research with 2 cycles which is carried out by simulating learning videos in each cycle. The result of the implementation of cycle 1 and 2 is concluded that contextual learning SQ3R type is able to increase the reading comprehension skill of students, students’ motivation increased by being active in learning, and teacher is more professional in delivering material. So that learning runs effectively and the learning objectives are successfully achieved.